Shooting free throws under pressure: a social media self-talk intervention - Gomez Souffront, Mavrantza, A. M.; Bigliassi, M (Journal of Clinical Sport Psychology, 2024)
The present study sought to investigate the effects of a self-talk intervention on free-throw performance under pressure. The experimental manipulation was designed using a video from a social media platform. Thirty male college basketball players were randomly assigned into two groups (i.e., control and experimental). The experimental protocol incorporated three trials of three free throws each. Psychophysiological stress was assessed by use of heart rate variability. The illusion of pressure was created using arena recordings of large crowds along with instructions for participants to visualize a high-pressure scenario. The results indicate that the self-talk intervention was sufficient to improve free throw shooting accuracy during the postintervention phase. Short-term heart rate variability reduced significantly for the control group and remained relatively stable for the experimental group. Self-talk appears to influence free throw accuracy during situations of psychosocial stress by inhibiting the influence of negative thoughts on peripheral physiological reactions and movement automaticity.